MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Safitri, Juliana; Zanthy, Luvy Sylviana; Hendriana, Heris (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research did from the low ability phenomena of mathematical communication of SMP in Purwakarta. The low skill ability of mathematical communication can be seen from the lack of students in completing the test of mathematical communication form to provided in the first research, the purpose of this research was to examined the improvement of CTL (Contextual Teaching and Learning) skill with traditional learning and the methodology of this research using quasi-experimental method which consist of two classes. The first is experiment class treated using CTL and the second is control class treated traditional learning. The population of the research taken was students of SMP Negeri 1 Babakan Cikao and a randomly selected sample of consist of 30 students of class VII A as the experiment. Class and 30 students of class VII D as control class. The instrument of this research used 6 items about mathematical communication description form, that has been tested the validity, reliability and distinguish of power form indexed difficulty. Based on the result of data analysis have concluded that the improvement of mathematical communication ability in SMP Negeri 1 Babakan Cikao by using CTL approach is better than traditional learning.